2007
DOI: 10.2111/06-082r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weaning Date and Prepartum Protein Supplementation on Cow Performance and Calf Growth

Abstract: Two experiments evaluated effects of weaning date on cow body condition score (BCS) and calf growth. In Experiment 1, 134 March-calving cows were used in a four-year experiment. Calves were weaned 18 August or 7 November and cows were fed 0 or 0.45 kg protein supplement (42% crude protein) three days per week from 1 December to 28 February while grazing upland range in a 2 by 2 factorial arrangement of treatments. In Experiment 2, spring calving cows (year 1, n 5 97; year 2, n 5 104) were assigned randomly to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 27 publications
8
26
2
1
Order By: Relevance
“…However, no difference in BW of supplemented and nonsupplemented cows was noted at weaning (P = 0.16) but there was a tendency (P = 0.08) for supplemented cows to have a greater BCS than nonsupplemented. Our data agrees with numerous reports documenting the effect of protein supplementation of cows consuming poor quality forage during late gestation on BW and BCS (Randel, 1990;Bohnert et al, 2002;Stalker et al, 2007).…”
Section: Cow Performancesupporting
confidence: 93%
See 3 more Smart Citations
“…However, no difference in BW of supplemented and nonsupplemented cows was noted at weaning (P = 0.16) but there was a tendency (P = 0.08) for supplemented cows to have a greater BCS than nonsupplemented. Our data agrees with numerous reports documenting the effect of protein supplementation of cows consuming poor quality forage during late gestation on BW and BCS (Randel, 1990;Bohnert et al, 2002;Stalker et al, 2007).…”
Section: Cow Performancesupporting
confidence: 93%
“…At calving, the difference in BW and BCS between HBCS and LBCS cows remained (P < 0.001), and at weaning, the HBCS cows were still 29 kg heavier (P < 0.001) and had a 0.5 greater (P < 0.001) BCS than LBCS cows. These data agree with those reported by Stalker et al (2007) who showed cows with greater BW and BCS at the beginning of the last trimester of gestation also had greater BW and BCS at calving and at weaning.…”
Section: Cow Performancesupporting
confidence: 92%
See 2 more Smart Citations
“…Because Jun-and Augcalving cows rapidly gained BCS postweaning, Jun-and Aug-born calves could be weaned at older ages without decreasing cow BCS at weaning below the BCS of Mar-calving cows at weaning. Stalker et al (2007) demonstrated calf efficiency of gain is improved with later weaning dates and that it is preferable to keep the calf with the cow if it does not compromise cow BCS or rebreeding performance. 1 Number of pregnant cows that started the study each year.…”
Section: Effects Of Calving Date On Weaned Calf Performancementioning
confidence: 99%